Analisis Performa Sistem Pemantauan Suhu Dan Kelembaban Berbasis Wireless Sensor Network - Da'imul Royan; Rakhmadhany Primananda; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Utilization of more adequate technology to support agricultural resources needs to be done. One of the technologies required is a temperature monitoring system and humidity based wireless sensor network environment with good performance to give a comparable value to the observed parameters premises. There are many sensor devices that serve to measure temperature and humidity, accuracy is one of the parameters that can be used to determine it. Once the selected component requires delivery scheduling method with time division to avoid the possibility of data transmission collision, time synchronization is required to support scheduling method. After the facility is formed, it is necessary to conduct performance tests to determine the performance of the system whether in accordance with field conditions. Parameters in system performance testing are system functionality, sensor response to temperature and humidity changes, sensor accuracy comparison in variations of time period of use on farmland, comparison of delivery delay in variation of distance between nodes and RAM usage. From the test results show that all the functionality of the system can work well with a 100% success percentage. DHT11 has a response time of 10.4 seconds - 10.9 seconds each for temperature and humidity measurements, the large range of values influences the temperature reader. DHT11 has a relative error range of 1.2 - 1.5% and 5.6 - 6.3% respectively for temperature and humidity measurements, duration of use has no effect on accuracy. The system has the largest delivery delay at a distance of 70m node is 19Î¼s, the more distant the resulting delay the greater. The largest use of RAM reached 47% when sending messages on sensor nodes.